METHODOLOGICAL FOUNDATIONS IDENTIFYING DAMAGES FOR THE COUNTRY UNDER RESPONSIBILITY PRINCIPLE - Drozd I.; Drozd N.; Zayats N.; Krasnikov D. (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Essence, evolution of regulation and features of damage for the state is considered. Method of their calculation and effects on liability of officers is defined.